2000
DOI: 10.1096/fj.99-1010fje
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cardiac hypertrophy and altered blood pressure control in transgenic rats with the human tissue kallikrein gene

Abstract: To evaluate the cardiovascular actions of kinins, we established a transgenic rat line harboring the human tissue kallikrein gene, TGR(hKLK1). Under the control of the zinc-inducible metallothionein promoter, the transgene was expressed in most tissues including the heart, kidney, lung, and brain, and human kallikrein was detected in the urine of transgenic animals. Transgenic rats had a lower 24-h mean arterial pressure in comparison with control rats, which was further decreased when their diet was supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 46 publications
7
81
0
Order By: Relevance
“…Consistent with the anti-fibrotic effect of BK in cardiac fibrosis (29) we have recently reported that BK reduced renal fibrosis (30). Using the UUO-induced model for renal fibrosis we showed that BK B2-/-mice have significantly higher tubulointerstitial fibrosis than wild type mice.…”
Section: In This Issue Of Jasnsupporting
confidence: 78%
“…Consistent with the anti-fibrotic effect of BK in cardiac fibrosis (29) we have recently reported that BK reduced renal fibrosis (30). Using the UUO-induced model for renal fibrosis we showed that BK B2-/-mice have significantly higher tubulointerstitial fibrosis than wild type mice.…”
Section: In This Issue Of Jasnsupporting
confidence: 78%
“…Furthermore, the mice are housed in a pathogen-free environment. Transgenic rats overexpressing the human tissue kallikrein gene, TGR(hKLK1), and their transgene negative littermates were generated as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
“…4 Transgenic rats overexpressing tissue kallikrein (TK) develop less cardiac hypertrophy and fibrosis than do wild-type rats. 5 In addition, evidence provided by ourselves 3 and Meneton et al 6 indicates that genetically ablating B2R or TK in 129/J mice results in dilated decompensated cardiomyopathy. This is in keeping with the recent discovery that deletion polymorphism of human B2R gene is associated with an exaggerated cardiac growth response to physical training in healthy volunteers.…”
mentioning
confidence: 99%